Translating Nucleic Acid Amplification Assays to the Microscale: Lab on a Chip for Point-of-Care Molecular Diagnostics - G. Mauk, Michael; Song, Jinzhao; Tong, Yubing; H. Bau, Haim; Liu, Changchun (Current Analytical Chemistry, 2016)
Background: Nucleic acid amplification test (NAAT) provides the highest levels of sensitivity and specificity for sequence-specific detection of DNA and RNA associated with pathogens and diseases. Currently, these tests are largely limited to laboratory use, as they require considerable sample preparation and expensive instrumentation. However, emerging microfluidic lab-on-a-chip technology enables lowcost, easy-to-use, palm-sized NAAT devices, widening NAAT applications to point-of-care (POC) diagnostics. Here, we review the evolution of microfluidic-based molecular diagnostics with a focus on work that has been carried out in our laboratory as an instructive case study. Methods: We discuss technology pathways for integration of pathogen lysis, nucleic acid isolation, amplification, and quantitative detection of DNA and RNA in a microfluidic format suitable for POC diagnostics. In addition, novel microfluidic approaches for plasma extraction, and enzymatic amplification reaction-diffusion-based method (nuclemeter technology) for end-point quantification are described. Results: Simplifications in design and operation of the microfluidic-based molecular (nucleic acid) diagnostics can be realized with modifications to solid-phase extraction methods to isolate, purify, and concentrate nucleic acid; the use of isothermal amplification; pre-loaded, paraffin-encapsulated reagents; chemical heating; and Smartphone-based detection. Conclusion: The future development of microfluidic-based POC devices is to fully integrate multiple processes required for genetic analysis on a single microfluidic format platform. There is an urgent need for such inexpensive, POC, molecular diagnostic systems at the bedside, at home, in doctors’ and dentists’ offices, clinics, and pharmacies, and especially in resource-limited regions of the world.
Keywords: molecular diagnostics